Предмет: Математика,
автор: Милаха2021
Найдите корни уравнения (—4 х — 3)(3 х + 0,6) = 0
Ответы
Автор ответа:
0
-4x*3x-4x*0.6-3*3x-3*0.6=0
-12x в квадрате -2,4х-9х-1,8=0
-12х в квадрате -11,4х-1,8=0
Д=11,4*11,4-4*(-12)*(-1,8)=129,96-86,4=43,56=6,6 в квадрате
х=(11,4+6,6)/(2*(-12))=18/(-24)=-0,75
х=(11,4-6,6)/(2*(-12))=4,8/(-24)=-0,2
-12x в квадрате -2,4х-9х-1,8=0
-12х в квадрате -11,4х-1,8=0
Д=11,4*11,4-4*(-12)*(-1,8)=129,96-86,4=43,56=6,6 в квадрате
х=(11,4+6,6)/(2*(-12))=18/(-24)=-0,75
х=(11,4-6,6)/(2*(-12))=4,8/(-24)=-0,2
Автор ответа:
0
Спасибо большое)))
Похожие вопросы
Предмет: Химия,
автор: emily3298
Предмет: Английский язык,
автор: dragonlightto
Предмет: Астрономия,
автор: conya308
Предмет: Алгебра,
автор: лейла228
Предмет: Алгебра,
автор: папапапц4к4